Comparison of perioperative outcomes among patients with exophytic, mesophytic, and endophytic renal tumors undergoing robot‐assisted partial nephrectomy. (6th June 2022) - Motoyama, Daisuke; Ito, Toshiki; Sugiyama, Takayuki; Otsuka, Atsushi; Miyake, Hideaki
Abstract : Objectives: It has been well documented that partial nephrectomy for completely endophytic renal tumors is a highly challenging procedure accompanied by several technical difficulties even with the assistance of a robotic surgical system. This study aimed to compare perioperative variables among patients with exophytic, mesophytic, and endophytic renal tumors undergoing robot‐assisted partial nephrectomy. Methods: This study retrospectively included 265 consecutive patients with localized small renal masses undergoing robot‐assisted partial nephrectomy at our institution. In this study, completely endophytic tumor was defined as the mass totally covered by renal healthy parenchyma, and according to the points for the 'E' domain of RENAL nephrometry score based on preoperative computed tomography, subjects were classified into three groups as follows: exophytic, mesophytic, and endophytic tumor groups, and perioperative outcomes among these groups were compared. Results: Of 265 patients, 127, 112, and 26 were classified into the exophytic, mesophytic, and endophytic tumor groups, respectively. A significantly smaller tumor diameter was observed in the endophytic group than in the other groups ( P < 0.001), whereas the RENAL nephrometry score was significantly higher ( P < 0.001). In addition, the warm ischemia time in the endophytic tumor group was significantly longer than that in other groups ( P = 0.009); however, no significant difference in the trifecta achievement was noted among the three groups. Conclusions: This study suggests that robot‐assisted partial nephrectomy for patients with completely endophytic tumors can be regarded as a feasible approach without marked impairment of perioperative outcomes; however, further investigation of the long‐term functional and oncological outcomes in these patients is required.